Sosialisasi Pengembangan Media Pembelajaran Berbantuan Adobe Flash Berbasis Kooperatif untuk Meningkatkan Kemampuan Spasial Siswa Kelas V UPT SD Negeri 064023 Medan - Panjaitan, Hendrikson; Binnner Sihaloho (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service aims to: (1) Provide education and training on the development of cooperative-based Adobe Flash-assisted learning media to training participants (teachers), (2) Improve spatial and good mental attitudes, to compile their own open modules. This community service was carried out at UPT SD Negeri 064023 Medan. The partner in this activity is UPT SD Negeri 064023 Medan. The methods in this community service are: (1) Analyze the situation and needs, (2) After analyzing the situation and needs, the next step is to determine the objectives of PKM, (3) Design training models, mentoring and workshops, (4) Expert validation, (5) Implementation, (6) Evaluation of the results of this activity include: (1) participants understand and can create teaching materials in the form of modules, lks, (2) the motivation of participants to create their own teaching modules increases.